The Role of the Large T Antigen in the Molecular Pathogenesis of Merkel Cell Carcinoma - Myrda, Julia; Bremm, Franziska; Schaft, Niels; Dörrie, Jan (Genes, 2024)
The large T antigen (LT) of the Merkel cell polyomavirus (MCPyV) is crucial for Merkel cell carcinoma (MCC), a rare but very aggressive form of neuroendocrine skin cancer. The clonal integration of MCPyV DNA into the host genome is a signature event of this malignancy. The resulting expression of oncogenes, including the small T (sT) antigen and a truncated form of the LT (truncLT), directly contribute to carcinogenesis. The truncation of the C-terminus of LT prevents the virus from replicating due to the loss of the origin binding domain (OBD) and the helicase domain. This precludes cytopathic effects that would lead to DNA damage and ultimately cell death. At the same time, the LxCxE motif in the N-terminus is retained, allowing truncLT to bind the retinoblastoma protein (pRb), a cellular tumor suppressor. The continuously inactivated pRb promotes cell proliferation and tumor development. truncLT exerts several classical functions of an oncogene: altering the host cell cycle, suppressing innate immune responses to viral DNA, causing immune escape, and shifting metabolism in favor of cancer cells. Given its central role in MCC, the LT is a major target for therapeutic interventions with novel approaches, such as immune checkpoint inhibition, T cell-based immunotherapy, and cancer vaccines.
CRIS-Team Scopus Importer:2024-10-04
Keywords: antigen-based immunotherapy; cell cycle regulation; immune escape; Merkel cell carcinoma; Merkel cell polyomavirus; viral carcinogenesis